PLIE- A Light-weight Image Encryption for data Privacy in mobile cloud storage - Sankari, M.; Ranjana, P. (International Journal of Engineering and Technology, 2018)
Data privacy is the greatest challenge of mobile cloud computing to secure the image data. Traditional encryption techniques are mainly suitable for text data than image data. In this paper, we introduce a method called Privacy-preserving light weight Image Encryption (PLIE) to protect the image data in mobile cloud, maintains the userâ€™s privacy by keeping metadata in mobile. It improves the throughput, speed-up the encryption time in mobile and minimize the complexity. Basically,three processes handled on image data such as split, distribute and scramble (SDS) in mobile for maintaining the userâ€™s privacy and store it in cloud. For our analysis of gathering images, the encryption time of the PLIE method implemented in python language resulted as approximately 50% reduced than AES. We measured the performance analysis of existing method(AES) with the proposed method(PLIE) by various parameters. In addition,we present some security attacks to evaluate the level of security.Â Â